Intelligent environment friendly rest room system - Nor Alina Khairi (School of Microelectronic Engineering, University Malaysia Perlis, 2011)
A public restroom was equipped with many facilities such as hand basins for hand wash, toilet, baby changing rooms and even showers. Nevertheless, using it incorrectly can cause a huge amount of waste such as energy and water which can affect the environment. In this paper, a smart system was designed to overcome the energy and water waste. The system was based on the embedded system which acted as to monitor the environment within the restroom. The main controller used was the AVR microcontroller atmega64 and relevant signal process circuitry to design the controller system. Infrared Light Emitting Diode (IR LED) and Light Dependent Resistor (LDR) sensors were used to detect user presence for the system to operate automatically.